PENGARUH KONSUMSI SUSU KEDELAI TERHADAP PRODUKSI ASI IBU MENYUSUI DI KLINIK KARTIKA HUSADA - Qurothul; Tut Rayani Aw; Anik Sri Purwanti (Maternity and Neonatal : Jurnal Kebidanan, 2025)
For the first six months and until the child is two years old or older, exclusive breastfeeding is advised. Babies may not receive the best nourishment possible if there is insufficient or inconsistent production of breast milk. Nuts have long been consumed by people in many nations, including Indonesia, and are a significant source of vegetable protein and fat. In addition to being free of chemical poisons, soybeans are a good source of calcium, iron, protein, potassium, phosphorus, and vitamin B complex. Isoflavones (phytoestrogen hormones), which are estrogen hormones the body naturally produces and which can aid the mammary glands in producing breast milk, are occasionally also found in soybeans. This study sought to ascertain how soy eating affected nursing moms' supply of breast milk. Purposive sampling methods, a one-group pre-post design, and paired t-test data analysis were all employed in this investigation. According to the study's findings, postpartum women' breast milk production increased when they were given soy milk (Sig. <0.05). The findings demonstrated that providing soy milk to postpartum moms increased their production of breast milk. The statistical analysis's findings demonstrated that the impact of providing soy milk was statistically significant, with a t-count value (5.385) that was higher than the t-table (1.699) and a significant value of 0.00 (less than Î± = 0.05). According to the study's findings, breastfeeding moms' supply of breast milk is impacted by their soy intake